2019
DOI: 10.3889/oamjms.2019.783
|View full text |Cite
|
Sign up to set email alerts
|

Botulin Toxin Use in Scars/Keloids Treatment

Abstract: Botulinum toxin (BTX) is a neurotoxin protein derived from the Clostridium botulinum bacterium that inhibits the release of acetylcholine at the neuromuscular junction level whose effects has been used for many years to treat a variety of muscular/neuromuscular conditions and more recently also for cosmetic use. BTX has experimented in some dermatological conditions which include scar prevention and treatment with good results. The complex mechanism underlying those results is not completely understood b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…The observations of sialidase activity with the RDE titration method showed that each isolate had various activity values. Overall, three isolates, B025, B048, and B060, had RDE titers of 2 4 ; four isolates, B023, B027, B033, and B055, had RDE titers of 2 5 ; and two isolates, B043 and B047, had RDE titers of 2 7 . B059 had an RDE titer of 2 6 , and the B028 code isolate had a higher titer than that of the other isolates with 2 8 dilutions of HI.…”
Section: Synthesis Of Sialidase and Determination Of C Perfringens Is...mentioning
confidence: 96%
See 1 more Smart Citation
“…The observations of sialidase activity with the RDE titration method showed that each isolate had various activity values. Overall, three isolates, B025, B048, and B060, had RDE titers of 2 4 ; four isolates, B023, B027, B033, and B055, had RDE titers of 2 5 ; and two isolates, B043 and B047, had RDE titers of 2 7 . B059 had an RDE titer of 2 6 , and the B028 code isolate had a higher titer than that of the other isolates with 2 8 dilutions of HI.…”
Section: Synthesis Of Sialidase and Determination Of C Perfringens Is...mentioning
confidence: 96%
“…Neurotoxins from Clostridium have been extensively studied in medical applications in the past 25 years. It has been used as a therapy for cases of muscle spasms and chronic pain and for cosmetic purposes [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…BTA has been available for clinical use for more than 30 years and its efficacy and safety are well proved. Nowadays, an increasing number of studies have showed that BTA injections inhibit the formation of HS 2‐5 . Moreover, our previously published random clinical trial found that the injection of BTA in the early postoperative could decrease the scar formation, reduce the scar width, and make the overall appearance more satisfactory 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The clear mechanisms of action of BoNT-A in scar prevention and treatment are still not clearly understood; however, action on wound tension, collagen, and fibroblasts are proposed [15]. Moreover, it has shown that BoNT-A inhibits release of different substances like (TGF)-b, calcitonin gene-related peptide (CGRP), substance P, and glutamate, thus modulating cutaneous inflammation and wound healing [20].…”
Section: Discussionmentioning
confidence: 99%